Using EFLRAI to Spot Reading Anxiety on Junior High School 1 Bukittinggi Students - Sherly Oktaviani; Yetti Zainil (Universitas Negeri Padang, 2021)
Based on the author’s experience in teaching English at Junior High School 1 Bukittinggi, many students find it hard when it comes to reading. Their English score is always good except for the reading section. The Author suspects that the students are experiencing reading anxiety, but the cause is not known yet. Considering these problems, the right thing to do is to run the reading anxiety test towards the students. This test is not only to find their level of reading anxiety, but also the factors of their reading anxiety. The istrument that is used to run the test is EFLRAI which is an instrument that specifically designed for non-English major students who are suspected of experiencing reading anxiety. EFLRAI stands for English as a Foreign Language Reading Anxiety Inventory. It is an instrument to measure reading anxiety developed by Masoud Zoghi (2012). It consists of three sections that contain several questions. These questions will help the teacher to know what the causes of reading anxiety for each student are. As a likert type questions instrument, EFLRAI has 4 point; 1 (totally disagree), 2 (somewhat disagree), 3 (somewhat agree), and 4 (totally agree) with the high total score means high reading anxiety. By using EFLRAI instrument to run the reading test the teacher can spot students with reading anxiety as soon as possible and point out the factors cause reading anxiety to students. After knowing the factors, teacher can help students to overcome their anxiety in the right way.